Falls in young children with minor head injury: A prospective analysis of injury mechanisms. (8th May 2015) - Samuel, Nir; Jacob, Ron; Eilon, Yael; Mashiach, Tania; Shavit, Itai
Abstract: Background : Fall is a common mechanism of injury (MOI) in young children and an important risk factor for traumatic brain injury (TBI). Most children who fall have a minor head injury (MHI), defined as a blunt head trauma that occurred in a patient who is conscious and responsive. Objective : To seek a possible association between MOI and injury severity. Methods : A single centre cohort study was conducted. Data were collected on patients aged 0–2 years with MHI. Clinically-significant TBI (csTBI), defined as head injury resulting in death, intubation or neurosurgery, was the primary outcome measure. Traumatic finding on CT scan (TFCT) was the secondary outcome measure. Results : Five hundred and ninety-five patients were analysed. Eight types of falls were identified: from ground-level, down stairs, from a bed, from a changing table, from furniture, from adult-hold, from a playground-device and from a stroller/baby-carriage. One patient (0.16%) had csTBI. Thirty-one (5.2%) underwent CT scans, TFCT was diagnosed in 17 (2.8%) patients; 10 (1.7%) linear skull-fractures, two (0.3%) depressed skull-fractures and five (0.8%) intracranial haemorrhages. Regression analysis did not reveal a statistically significant association between any of the MOI and the presence of TFCT. Conclusions : The risk for csTBI was low and no association was found between MOI and injury severity.